An introduction to active distribution networks islanding issues - Jouybari-Moghaddam, H.; Hosseinian, S. H.; Vahidi, B. (2012 Proceedings of 17th Conference on Electrical Power Distribution Networks, 2012)
Nowadays distributed generation (DG) is of main concern due to growing power demand. Due to increasing DG penetration, the incorporation of DGs into existing system and their independent operation as power islands needs to be addressed properly in standard and practical work recommendations. This paper generally introduces the chief issues in unintentional islanding and its prohibition by the standard. Furthermore, it presents examples showing feasibility of stable and reliable intentional islanding. Accordingly, the concept of islanding detection as a requirement for either preplanned islanding operation or unplanned-islanding-prohibition, is introduced. Considering the aforementioned prohibition and the validation of feasible successful islanding operation, this paper concludes that, in order to avoid unnecessary loss of generation specially for sensitive and high priority loads, if we are going to establish regulations, we must take into account electric power systems facility classifications and variety of possible events that may result in islanding.